Locomotor and high-speed performance profiles in women’s and men’s FIFA World Cup football - Gutev, Grigor Krasimirov; Dimova, Iva (Tanjungpura Journal of Coaching Research, 2026)
Background The only published elite comparison that uses a common measurement system for both genders reports that men cover a total distance of about 3–5% farther and cover significantly more high-speed distance during UEFA Champions League matches. Exposure-normalised comparisons of locomotor performance between the women’s and men’s international games are scarce. Objectives This study compared the 2023 FIFA Women’s World Cup with the 2026 FIFA World Cup. Methods Player-match (1,898 women; 3,288 men) and team-match (128; 208) observations were harmonised and normalised to a per-90-minute basis. Because the datasets used non-identical speed zones, inference was restricted to bin-independent outcomes: total distance, distance below and above 7 km·h⁻¹, and peak speed. Group differences were quantified using effect sizes (Cohen’s d). Results Running distance above 7 km·h⁻¹ did not differ meaningfully between tournaments (6,338 vs 6,255 m·90⁻¹; d = −0.04), and women ran a greater proportion of their distance above walking pace (63.1% vs 60.3%). Men accumulated more low-speed distance (+13.5%; d = 0.87) and reached higher peak speeds (+8.4%; d = 0.83), a difference evident across all outfield positions but not among goalkeepers. Substitutes covered 20–30% more distance per minute than starters in both tournaments, without higher peak speeds. Conclusion Once exposure is controlled, the tournaments are similar in running volume but differ in profile: men are faster at the top end and accumulate more low-speed locomotion, whereas the women’s game is proportionally more running-dominated. Sex and format remain confounded.